Oscillations of Numerical Solutions for Nonlinear Delay Differential Equations in the Control of Erythropoiesis - Qi Wang; Jiechang Wen (Discrete Dynamics in Nature and Society)
We consider the oscillations of numerical solutions for the nonlinear delay differential equations in the control of erythropoiesis. The exponential θ-method is constructed and some conditions under which the numerical solutions oscillate are presented. Moreover, it is proven that every nonoscillatory numerical solution tends to the equilibrium point of the continuous system. Numerical examples are given to illustrate the main results.